Typification of Iberian names in Viola Sect. Melanium (Violaceae) with nomenclatural notes - Magrini, Sara (Phytotaxa, 2019)
Based on the analysis of relevant literature and of specimens from European herbaria, nomenclatural types for seven out of the nine Iberian names belonging to the genus Viola Sect. Melanium are designated here: Viola demetria (G), V. kitaibeliana subsp. machadeana (COI), V. kitaibeliana subsp. trimestris (M), V. langeana (C), V. montcaunica (MA), V. nevadensis (G), and V. tricolor subsp. olyssiponensis (P).